(untitled) (SAARC Journal of Agriculture, 2025)
An on-station feeding experiment was carried out to study the effect of age on feed intake and growth performance of Red Chittagong Cattle bulls (RCC) fed the same plane of nutrition for 90 days at Pachutia Farm, Bangladesh Livestock Research Institute, Dhaka. Before the feeding trial, 15 RCC bulls in four age groups were split up into four groups and properly dewormed. The average live weight of the four age groups—9–10 months, 15–16 months, 21–22 months, and 27–28 months—was 57.75, 86.40, 112.00, and 160.00 kg, respectively. There were four animals in the 9–10 months age group, five in the 15–16 months group, and three in each of the 21–22 and 27–28 months groups. The data were analyzed using analysis of variance for a Completely Randomized Design (CRD). Bulls in the 27–28-month age group consumed considerably more DM (Dry Matter), OM (Organic Matter), CP (Crude Protein), and ADF (Acid Detergent Fiber) per day (p<0.01) than other groups and increased significantly (p<0.01) as it grew older. Average daily weight gain significantly increased with age, highest in 27–28-month bulls and lowest in 9–10-month bulls (p<0.05). FCR was found in the 9-10 months age group significantly (p<0.05) lower and higher in the 27-28 months age group. As per the current findings, RCC bulls aged 9–10 months, 15–16 months, or 21–22 months exhibited higher Feed Conversion Ratio (FCR) performance compared to those aged 27–28 months. SAARC J. Agric., 23(1): 175-183 (2025)